MEMBENTUK KARAKTER ISLAMI DI ERA DIGITAL: TANTANGAN DAN SOLUSI - Umroh, Hayail; Habiburrahim; Buhori Muslim (Ta lim Jurnal Pendidikan Agama Islam dan Manajemen Pendidikan Islam, 2025)
Character building in the digital era has brought significant transformations in human life, including in the field of education. Technological advancements, such as the internet, social media, and other digital devices, have provided unlimited access to information. This article aims to explore how Islamic religious education can play a role in building Islamic character in the midst of the digital era and what challenges arise within it. This research uses a descriptive qualitative method with a literature study approach. The research results show that the formation of Islamic digital learning provides a significant opportunity to shape a generation that is not only intellectually smart but also possesses spiritual depth and moral integrity. By touching on various aspects of students' personalities, this design is capable of providing a holistic approach in building a strong Islamic character.